Seeing Writing Whole: The Revolution We Really Need - Keith Rhodes (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
Composition classes have difficulty achieving the aims of the CCCC position statement entitled Students’ Right to Their Own Language, for reasons related to why we have difficulty integrating calls for building rhetorical listening more fully into our curricula. A fundamental assumption that writers alone are responsible for the success of written communication leads to results that sustain privileged discourse and upset any sense that readers, too, have an obligation in any written transaction. A field of Writing, properly constituted, needs to challenge that assumption of readerly privilege overtly so that we can shift toward teaching students better ways to manage that entire transaction; meanwhile, we should emphasize practices that weaken the grip of readerly privilege, such as Elbow’s integration of the vernacular into writing and expanded efforts to use Young’s code-meshing approaches with broader audiences of students.
Keywords: Creative Writing